Laser optoacoustic diagnostics of femtosecond filaments in air using wideband piezoelectric transducers. (25th July 2016) - Uryupina, D S; Bychkov, A S; Pushkarev, D V; Mitina, E V; Savel'ev, A B; Kosareva, O G; Panov, N A; Karabutov, A A; Cherepetskaya, E B
Abstract: New opportunities in ultrasound diagnostics of femtosecond laser filaments with wideband piezoelectric transducers are considered. Transverse spatial resolution better than 100 microns is demonstrated in the single and regular multiple filamentation regime making path toward 3D filament tomography. The simple analytical model of the cylindrical acoustic source fitted well with the experimental data.